La literatura como impronta en la conformación de la historia: un análisis desde el círculo delmontino - Garnica, Jacqueline Murillo (Acta Hispanica, 2017)
This article proposes to highlight the importance and influence of the literary gatherings of Domingo Del Monte in the formation of a national identity originated by nineteenth century Cuban literature. Its relevance consists in how this movement has been fundamental in laying the foundations of a national consciousness and served as platform based on the narrative as testimony in the context of a colonialist situation that prevailed in the isle of Cuba in the nineteenth century. The Del Monte literary gatherings were responsible for the support of a small group of writers and accomplished a representation of a certain sector of minorities of color, not in the sense of being subject to studies, but conferring them a featured place in Cuban literature, because of their literary value and testimonies of reality. The relationships that were built between history and literature left a permanent mark in the Cuban anti-slavery narrative.The relation developed in the investigation between history and literature formed the basis of the study and analysis that had its genesis in the investigative work leading to a dissertation in Spanish and Hispanic American literature.